Analisis inovasi produk pada ekonomi kreatif sektor kerajinan galeri Batik Tabir Riau di Kota Pekanbaru - Shafira Amalia Ramadhani (Pelantar Press, 2021)
This research aims to increase creative economy competitiveness in Pekanbaru city specifically for batik craft sub-sector. This research was conducted with descriptive and quantitative methods, reffering to Galeri Batik Tabir Riau Ranis product innovation. The research data is composed of primary and secondary data. To obtain primary data, researcher uses observations, focused discussion and interview methods, and for the secondary data refers to Central Agency on Statistics Indonesia, literature books, journals, and internet. From the questionnaire data and focused discussion process, this research can be conclude that using SO strategy, that is utilize the power of opportunity, can increase economy competitiveness on Galeri Batik Tabir Riau Rani.